Evaluation of COVID‐19 coagulopathy; laboratory characterization using thrombin generation and nonconventional haemostasis assays. (5th September 2020) - White, Danielle; MacDonald, Stephen; Edwards, Tara; Bridgeman, Chris; Hayman, Megan; Sharp, Megan; Cox‐Morton, Sally; Duff, Emily; Mahajan, Swati; Moore, Chloe; Kirk, Melissa; Williams, Richard; et al.
Abstract: Introduction: Patients with COVID‐19 are known to have a coagulopathy with a thrombosis risk. It is unknown whether this is due to a generalized humoral prothrombotic state or endothelial factors such as inflammation and dysfunction. The aim was to further characterize thrombin generation using a novel analyser (ST Genesia, Diagnostica Stago, Asnières, France) and a panel of haematological analytes in patients with COVID‐19. Methods: Platelet poor plasma of 34 patients with noncritical COVID‐19 was compared with 75 patients with critical COVID‐19 (as defined by WHO criteria) in a retrospective study by calibrated automated thrombography and ELISA. Patients were matched for baseline characteristics of age and gender. Results: Critical patients had significantly increased fibrinogen, CRP, interleukin‐6 and D‐dimer compared to noncritical patients. Thrombin generation, in critical patients, was right shifted without significant differences in peak, velocity index or endogenous thrombin potential. Tissue plasminogen activator (tPA), tissue factor pathway inhibitor (TFPI) and vascular endothelial growth factor (VEGF) were significantly increased in the critical versus noncritical patients. Critically ill patients were on haemodiafiltration (31%; heparin used in the circuit) or often received escalated prophylactic low‐molecular weight heparin. Conclusion: These results confirm increased fibrinogen and D‐dimer in critical COVID‐19‐infected patients. Importantly, disease severity did not increase thrombin generation (including thrombin‐antithrombin complexes and prothrombin fragment 1 + 2) when comparing both cohorts; counter‐intuitively critical patients were hypocoaguable. tPA, TFPI and VEGF were increased in critical patients, which are hypothesized to reflect endothelial dysfunction and/or contribution of heparin (which may cause endothelial TFPI/tPA release).